Wahbah al-Zuhailī’s Epistemology of the Religious Freedom Concept: Between Maqāṣid Ḥifẓ al-Dīn and Human Rights - Lathifah, Anthin; Munawwarah, Lathifah; Achmad Gunaryo; Masduki, Anwar; Hidayatulloh, M. Arief (al-'adalah, 2025)
According to the classical ulama, maqāṣid ḥifẓ al-dīn includes faith and worship in the Islamic religion, but it is different from Wahbah al-Zuhailī, who developed the concept of ḥifẓ al-dīn as the epistemological basis of the law of religious freedom as a universal human right. The purpose of this article is to describe Wahbah al-Zuhailī's concept of religious freedom which is based on maqāṣid ḥifẓ al-dīn and the theology of freedom as a universal human right. This article is the result of literature research, where data on the concept of religious freedom according to Wahbah al-Zuhailī were analyzed using a content analysis approach and a thematic analysis related to the law on religious freedom. The results of the research conclude that the epistemology of religious freedom (al-hurriyah al-i'tiqādiyyah) according to Wahbah al-Zuhailī integrates the philosophical foundations of maqāṣid ḥifẓ al-dīn and the theology of religious freedom as an absolute human right from God. Based on the epistemological basis of this law, it produces two concept of freedom of religion: first, there should be no coercion to follow a particular religion as in the verse "lā ikrāha fī al-dīn (māni' min al-ikrāh 'ala al-dīn); second, freedom of religion (al-hurriyyah al-dīniyyah) is formulated in two areas, namely freedom of religion in the field of aqīdah which is absolute because it is in the region heart and freedom of religion in the field of worship as a form of religious expression. This freedom of worship is in the public domain and is determined based on state law which is oriented towards justice and the benefit of the people.